PENGUKURAN PENERIMAAN APLIKASI SICYCA MENGGUNAKAN METODE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Fattah, Abdurrahman; Hartati, Sulis Janu; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
SICYCA is the main website as media appreciation STIKOM Surabaya, the fact that not all SICYCA are used with maximum facilities by students. To know the success rate of a technology implementation, how high the student acceptance rate of SICYCA. The model used by researchers is the Unified Theory of Acceptance and Use of Technology ( UTAUT ). The instrument in this study was used questioner. The writer spread the questioner to students in STIKOM Surabaya in academic year 2010-2013 in every major at STIKOM Surabaya. The writer used 200 students as the sample in this study. The research design was used Stratified Random Sampling method which was focused on separated the elements group of words in STIKOM Surabaya. Descriptive analysis, validity analysis, and reliability was used SPSS 16 software. Data analysis was used Structural Equation Model (SEM) and use AMOS 22 software to analysis the structural. From the results of the data analysis, it can be concluded as follows: 1) performance expectancy has an positive effect to intentions of using SICYCA. 2) effort expectancy has an positive effect to the intentions of using the SICYCA. 3) social influence do not positive effect significantly to the intention of using the SICYCA. 4) facilitating conditions do not have an positive effect to the SICYCA utilizing. 5) behavioral intention has an positive effect to the use of behavioral SICYCA.